Parameter Space Design of a Guest-Host Liquid Crystal Device for Transmittance Control - Seung-Min Nam; Seung-Won Oh; Sang-Hyeok Kim; Jae-Won Huh; Eunjung Lim; Jinhong Kim; Tae-Hoon Yoon (Crystals, 2019)
A transmittance-control device requires a high transmittance difference between its transparent and opaque states. In this paper, we propose a systematic approach to find the condition for the maximum transmittance difference in a guest-host liquid crystal (GHLC) cell. To this end, we calculated the transmittance difference as we varied the cell gap and dye concentration. The transmittance of a GHLC cell is dependent on the alignment of dye molecules, cell gap, and dye concentration. We used a constant-transmittance contour map to find the condition for the desired transmittance of LC cells in each state and the transmittance difference of each LC mode. We experimentally confirmed that the design of a GHLC cell with the desired performance could be achieved through the proposed design process.